2019
DOI: 10.9734/ajmah/2019/46662
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Falls and Associated Factors among Construction Workers in Port Harcourt, Nigeria

Abstract: Background: Falls at construction sites are common occurrences with some resulting in fatalities. This study was to determine the prevalence and pattern of falls at construction sites in Port Harcourt Metropolis, Nigeria. Materials and Methods:This descriptive cross-sectional study sampled 340 construction workers from the two Local Government Areas of Port Harcourt Metropolis. A structured, close-ended, interviewer-administered questionnaire and Walk through Survey were the research instruments. Ethical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Workers who have not taken safety training were less likely to utilize PPE. This was supported by previous studies [8,[29][30][31][32][33][34][35][36]. Similarly, those who had not been trained on PPE utilization were less likely to utilize PPE in line with the previous studies [32,36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Workers who have not taken safety training were less likely to utilize PPE. This was supported by previous studies [8,[29][30][31][32][33][34][35][36]. Similarly, those who had not been trained on PPE utilization were less likely to utilize PPE in line with the previous studies [32,36].…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, inadequate or lack of training on PPE usage shows low PPE utilization [37]. This might be due to the reason training workers on safety and proper PPE use promotes [34,38]. It has paramount advantages on appropriate utilization of PPE [39] which is intended to prevent the risk of worksite injuries [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in China, construction accidents and the associated fatalities were deemed excessively high according to data from 2004, but subsequent safety policies have resulted in a decline in such incidents (Zhang, Zhang, Xu, and Chen, 2019). A study conducted in Nigeria revealed a significant prevalence of accidents, particularly falls from heights, within construction sites (Ngwu, Alabere, and Douglas, 2019). The United States recorded a fatal accident rate of 11.4 per 100,000 individuals during construction activities in 2003, whereas Spain reported a rate of 20.1 per 100,000 individuals in the same year (López, Ritzel, Fontaneda, and Alcantara, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Stair falls are the leading cause of job-related injuries and even workers' deaths on construction sites [4]. Falls often occur when a heavy load is placed on the back, balance is lost, the rails are slippery or there is no stair rail, or simply due to stumbles when descending [5][6][7].…”
Section: Introductionmentioning
confidence: 99%